Influence of dietary supplementation of modified tall oil, chromium nicotinate, and L-carnitine on bacon characteristics - Waylan, A.T.; O'Quinn, P.R.; Woodworth, J.C.; Owen, K.Q.; Unruh, John A.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty crossbred (PIC) gilts were used to determine the influence of feeding modified tall oil (MTO, 0 or .5% of diet), chromium nicotinate (0 or 50 ppb), and L-carnitine (0 or 50 ppm) on bacon quality characteristics. Supplementation of MTO improved bacon slice firmness. Dietary additions of MTO, chromium nicotinate, and L-carnitine to diets for growing and finishing swine had minimal effects on other bacon characteristics. Therefore, producers probably can take advantage of any improvements in production or carcass cutability from these feed supplements without affecting bacon quality.
Keywords: Swine; Bacon; Modified tall oil; Chromium nicotinate; L-Carnitine